ANALISIS KEBUTUHAN PENYEDIAAN RUANG PARKIR AKIBAT BEROPERASINYA RUMAH SAKIT KHARITAS BHAKTI DI JALAN SIAM KOTA PONTIANAK - Urip Puji Sulistiyo Adi; Komala Erwan; Slamet Widodo (JeLAST : Jurnal Teknik Kelautan , PWK , Sipil, dan Tambang, 2016)
Improvement of the quality  health infrastructure in Pontianak, has yet to show equity and improvement in the quality of services the public expected, when viewed from the side of the physical facilities, medical equipment, medical personnel, medicines and other supporting facilities. To add to the health care Pontianak City Government allowed private parties to build health facilities are Kharitas Bhakti Hospital in Siam Street. The existence of these hospitals to meet the needs of public health facilities Pontianak City and surrounding areas. This is what causes the vehicle parked in Jalan Siam bodies, thus impeding the flow of traffic on Siam Street. The purpose of this study was to determine the amount of traction that occurred and analyze the capacity and the need for parking spaces at the Kharitas Bhakti Hospital. The method applied in this research is to conduct a survey on the ground to get the number of parked vehicles, namely by noting the number plates of vehicles entering and exiting. The analysis of the pull of the trip happened in Kharitas Bhakti hospital  of 290 smp/day. To pull the trip versus the number of patient beds (beds) of 3.62 smp / bed / day. For the needs of parking spaces, the highest capacity is equal to 112 motorcycles veh / hour, and the highest parking capacity for cas is 52 veh/hour. Number of parking plots needed Kharitas Bhakti Hospital for motorcycles as much as 161 parking plots, provided as many as 72 parking plots, and for as many as 50 car parking plots, which provided a total of 14 parking plots. Keywords : parking requirement, Kharitas Bhakti Hospital, parking space.